Una comparación de la tectónica de basamento de las cordilleras central y oriental (1996)
The Central Cordillera and symmetrically structured parts of the Eastern Cordillera, as the Santander massif, display high angle faults which, with respectto acentral suture (Central Cordillera) or a central dome (Eastern Cordillera) show by their inward dips a fan - array. These faults cause a compartmental division of the crystalline basement of the Central Cordillera into elongate antiforms, which alternate with synclines of infolded remnants of the Cretaceous cover. A similar compartmental division is achieved within the symmetric parts of the Eastern Cordillera by normal faults and within asymmetric parts of an easterly vergence by reverse faults. The sub-vertical attitudes of the faults and the presence of paired normal and reverse faults are taken as evidence for essentially vertical uplift (or "upthrow") tectonics.